Proton Therapy Machine Quality Assurance: An Institutional Experience - Oonsiri, Sornjarod; Oonsiri, Puntiwa (Journal of Thai Association of Radiation Oncology, 2025)
Proton therapy quality assurance (QA) is an important process to ensure that the patient’s treatment is accurate. There are daily, monthly, and annual QAs. This article explored experience and QA tool usage for the QA process: Sphinx Compact for daily QA, Logos system XRV-124 for monthly QA, and MP3-PL combined with PTW Bragg peak chamber type 34070 for annual QA, respectively. It could help to give the idea for the staff, which supports the new facility’s planning in the future.